Inhibitory effect of magnetic aqueous extract of Syzygium aromaticum L on two types of oral pathogenic bacteria - Wafaa Eid; Saba Al-Sultan; Rana Al-Sabaawi (Medicinski glasnik, 2025)
Aim: Magnetic fields affect all living things, which is why they are the subject of extensive research around the world. The aim of this study was to investigate the effects of different levels of static magnetic field on chemical behaviours of aqueous extract of Syzygium aromaticum L and their effect on selective oral pathogenic bacteria. Methods: This study utilized locally manufactured dipolar static magnetic fields with strengths between 1200 and 3200 Gauss, measured by a Sylocimol Residence magnetizer. Gram positive G (+) Streptococcus viridans and G negative (G-) Porphyromonas gingivalis strains were used in studies on the antimicrobial properties of S. aromaticum extract. Tests were carried out using the clove essential component (eugenol) and its functionalized extract to evaluate various bacterial inhibitions and establish whether there is a synergistic effect between the extract and subjected to the magnetic field. Results: Polyphenol extraction increased with eugenol content. The analytical method's reliability was confirmed by chromatograms of eugenol and eugenol acetate standards, demonstrating good separation of compounds. The selectivity of the method was guaranteed by the purity index of the eugenol and eugenol acetate peaks. The aqueous extract of S. aromaticum showed magnetic properties. The extract showed antimicrobial activity against two bacterial strains. Cell viability changed at different magnetic field intensities, and the inhibition zone for P. gingivalis increased significantly due to prolonged exposure. Conclusion: The magnetized extract inhibits both G (+) and G (-) bacteria when combined with clove extract.
Keywords: Anti-bacterial activity; Clove extract; Magnetized extract; Oral bacteria